Health-related quality of life in patients undergoing laparoscopic versus open hemihepatectomy: a secondary analysis of the ORANGE II PLUS randomised controlled, phase 3, superiority trialResearch in context - Bram Olij; Robert S. Fichtinger; Luca A. Aldrighetti; Mohammad Abu Hilal; Roberto I. Troisi; Robert P. Sutcliffe; Marc G. Besselink; Somaiah Aroori; Krishna V. Menon; Bjørn Edwin; Mathieu D’Hondt; Valerio Lucidi; et al. (The Lancet Regional Health. Europe)
Summary: Background: Health-related quality of life (HRQoL) has become a critical factor in determining the benefits of new surgical approaches on patients. The ORANGE II PLUS randomised trial compared laparoscopic (LH) and open (OH) hemihepatectomy in an international multicentre randomised controlled setting, with HRQoL as a secondary outcome. The aim of this study was to perform an in-depth analysis of the HRQoL outcomes. Methods: Between October 2013 and January 2019, 352 patients scheduled for hemihepatectomy, were randomly assigned to either LH or OH in a 1:1-ratio in 16 European centres. HRQoL was assessed using the EORTC-QLQ-C30 and QLQ-LMC21 modules, at baseline, hospital discharge, and at 10-days, 3-, 6-, and 12-months after discharge. Differences in functioning- and five selected symptom scales were compared between LH and OH over the cumulative periods from discharge to 3 months as well as to 12 months using a multivariable adjusted linear mixed regression model. The study was registered at ClinicalTrials.gov (NCT01441856). Findings: The modified intention-to-treat analysis included 332 patients (166 LH and 166 OH), with 40% female in LH and 42% female in OH. 1546 questionnaires (81% of maximum) were obtained. Cumulatively over the period from discharge to 3 months postoperatively, patients in the laparoscopic group reported better physical (difference 4.20 points; 95% CI 1.07–7.34) and social functioning (5.95 points; 95% CI 1.65–10.26), and lower pain (−6.41 points, 95% CI −10.01 to −2.82) and appetite loss (−7.29 points, 95% CI −11.59 to −2.99), compared to the OH group. Similar clinically relevant, but slightly attenuated, differences were reported over the cumulative period from discharge to 12 months after surgery. The largest difference was observed at 10 days after surgery. Interpretation: In this international randomised trial evaluating HRQoL, LH demonstrated better physical and social functioning, and less pain and appetite loss, compared to OH. These findings support the preferential use of the laparoscopic approach for hemihepatectomy in experienced centres. Funding: Maastricht University Medical Centre+, University Hospital RWTH Aachen, Cancer Research UK 12/048, European Association of Endoscopic Surgery, participating centres.